Privatization against public spaces (Raíces: Revista de Ciencias Sociales y Políticas, 2020)
This essay entitled: Privatization against public spaces, has the purpose of disclosing the negative impacts produced by a model of privatization of the common goods of the Central American peoples. This model derives from the capitalist system imposed by the great powers through the mechanism of immoral, illegal and illegitimate indebtedness, through which they privatize and plunder the natural and financial resources of the countries, leaving the people without water, food, education, housing and forcing them to leave their own land as a result of hunger and insecurity. This is the reality of the present Central American and in representation of the Network of Community Environmentalists of El Salvador. (RACDES) and the Jubileo Sur / Américas Network, I present these analyzes in the space of the XII Central American Congress of Anthropology held at the headquarters of the National Autonomous University of Nicaragua. UNAN-Managua.
Keywords: Debt; Privatization; common goods; public spaces